Evaluation of race performance after tendon injuries in race horses with special respect to lesion related parameters - Caliskan, G.; Seyrek-Intas, D.; Celimli, N. (Trakia University, 2022)
The study aimed to assess the race performance after injury of the palmar metacarpal tendon region in Thoroughbred and Arabian racehorses. A special scoring system was established to evaluate the performance of the horses for each race after the injury, objectively in this study. Thus, individual total race earnings, the rates of ranking among the top four in at least two and three races and the number of participated races after injury were also analysed. The performance scores after injury were found to be lower in tendinitis cases compared to peritendinitis cases (P=0.0004). It was found that the success rate was lower in cases with tendon lesions than in cases without lesions in terms of race performance after injury (P=0.006). Injuries causing tendon thickening and also tendon echogenicity alterations had negative effects on race performances after injury (P=0.01 and P=0.04, respectively). Also individual total race earnings were lower in cases with tendon thickening compared to those without thickening (P=0.02). According to the results of this study, it is recommended to take prophylactic measures for tendinitis in cases with tendon thickening and echogenicity changes detected by ultrasound in the early stages of tendinitis to be able to display a good race performance after injury.
Keywords: performance scores; thoroughbred; ultrasound; tendinitis; Veterinary medicine; SF600-1100; arabian; race performances